Suicide: a preventable phenomenon in adolescents - Jardim, Maria Helena de Agrela Gonçalves (2017)
The profound changes in environmental, ecological, socio-cultural, ideologi cal and familiar materials in the last decades, confront adolescents with situa tions of hostility often generators of mental disorders in particular suicide risk. These evidences advocate the imperious need to promote mental health and balance of individual/social citizens, particularly the younger ones. In this context, the author developed a cross-sectional study, correlational and infe rential statistics, whose aim is to “evaluate the level of suicidal risk of young students from 12 to 18 years of the Autonomous Region of Madeira Island (RAM), Portugal”. The representative sample is probabilistic and stratified, composed of 1557 adolescents of both genders, attending basic and secondary schools in the municipality of RAM whose average age is 15.2. The selected measuring instrument was the suicide risk scale of Stork which showed high internal consistency (Alfa de Cronbach = 0.91) and good reliability. Most youngsters show no suicidal risk (67.7). However, 16.8% of young people should be the subject of concern, as 10.1% reveal weak risk, 4.0% showed im portant suicidal risk and 2.7% suicidal risk is extremely important. There is an association between suicidal risk (p = 0.000) gender and age groups (p = 0.000), being the highest rates in the 15 to 18 age group. As schooling level in creases, the risk of suicide, on the basis of the number of failures, being most evident in those that failed once. Parents being married or not also influences the manifestation of suicidal risk (p = 0.003), being most evident in young people whose parents are not married. The fact that the adolescents deal or dealt with some disease (p = 0.038), drink or have drunk alcohol (p = 0.003) as well as not socializing with colleagues (p = 0.000); has significant influence on the suicidal risk. In the same way, taking or have taken drugs (p = 0.000) influence the suicide risk. These results are a contribution in the statistics field of action. To study the suicide risk is an incentive to the scientific community for future research and the development of strategic support programs with specific interventions to promote the mental health of young people and social and educational policies.